Socio-Demographic Determinants of Overweight and Obesity Among School Children in An Urban City of Central India - Garima Namdev; Mahesh Kumar Mishra; Dinesh Kumar Saxena; SwarnaKanta Likhar (Medsci Publications, 2015)
Background: Childhood obesity with all its adverse health consequences is growing at a very fast rate in developing countries. Identification of obese status during early childhood has substantial health benefits to the children and to the country. Present study aimed to assess prevalence of overweight and obesity and associated socio demographic factors amongst children in Bhopal city. Methods: A cross sectional descriptive study was conducted for 28 months among students of IX, X, XI, XII classes in both government and private schools of Bhopal. Multistage simple random sampling procedure was used. Anthropometric measurements and a pretested self-administered questionnaire comprised of socio demographic information were used for data collection. Results: In present study, 256 (5.6%) students were overweight and 46 (1.0%) were obese. Maximum numbers of 2.5% obese students were belonging to upper SES as compared to middle and lower SES. Conclusion: The overall prevalence of overweight and obesity was found more common in girls and among students of private schools. It was found more in children with their working mothers with higher education.